PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 26 BUKIT KERIKIL KABUPATEN BENGKALIS - Efida '; Lazim.N '; Otang kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT: This research is motivated by the low learning outcomes Mathematics fifth grade students of SDN 26 Gravel Hill, with an average grade 59.25. While the value of a minimum completeness criteria (KKM) mathematics is 65. Among the students of 20 people only 8 people reach KKM. This study is a Classroom Action Research (CAR) conducted aims to improve mathematics learning outcomes fifth grade students of SDN 26 Gravel Hill by applying the Problem Based Learning model. Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the results of studying the data obtained from the average results of study before action 59.25 increased to an average of 73.25 in the first cycle with an increase of 23.62%. In the second cycle increased to an average of 81 with an increase of 10.58% .Aktivitas teachers in the first cycle of the first meeting to obtain a percentage of 70% in both categories, at the second meeting has increased by 75% the percentage of both categories. Furthermore, the first meeting of the second cycle of teacher activity also increased with the percentage of 85% is very good category and at the second meeting of the second cycle increased again by 90% the percentage of very good category. Activity of students in the first cycle of the first meeting to obtain the percentage of 65% good category, at the second meeting have increased the percentage of 75% good category, in this cycle the students begin to understand the learning activities by implementing a Problem Based Learning model is characterized by the activity of students in the second cycle the first meeting increased with a percentage of 80% is very good category. At the second meeting of the second cycle increased by 90% the percentage of very good category. Results of the study in class V SDN 26 Gravel Hill proved that the application of problem-based learning model can improve learning outcomes mathematics fifth grade students of SDN 26 Gravel Hill.Keywords: Problem Based Learning, Mathematics Learning Outcomes